ANALYSIS OF THE IMPACT OF MAXIMUM VEHICLE LOAD AT THE AGE OF FLEXIBLE PAVEMENT (CASE STUDY OF THE ROAD SECTION OF HERA DILI TIMOR-LESTE - Junizia Elsa De Almeida; Koespiadi (Neutron, 2020)
The road network is a land transportation infrastructure that plays an important role in the transportation sector, especially for the balance of the distribution of goods and services, both from other regions. In this study, an analysis was conducted to find out how the influence of heavy vehicle volume increase on the service life of the road, while the method used was Bina Marga, the study was conducted by taking a case study on the Hera road section until Dili. This research is expected to find out how the service life of the road if the volume of heavy vehicles continues to increase. If the% of heavy vehicles increases, the thickness of the required surface layer will also be even greater. When% of vehicles or carrying heavy traffic loads are increased, the thickness of the existing layer cannot meet, because the calculation results with% of heavy vehicles increase by 10%, surface thickness 17.2 cm / This will cause the service life of the road to decrease because it is confirmed that the road will be damaged before the service period ends due to excessive load increase in heavy vehicles.